Long-term cognitive sequelae in a case of Wernicke's encephalopathy after allogeneic stem cell transplantation. Issue 2 (3rd March 2016) - Giovannelli, Fabio; Basagni, Benedetta; Potenza, Leonardo; Foschi, Valeria; De Tanti, Antonio
ABSTRACT: We describe the case of a non-alcoholic patient with chronic myeloid leukemia who developed iatrogenic Wernicke's encephalopathy (WE) following stem cell transplantation. Four years after the WE acute event, the patient's cognitive profile was mainly characterized by moderate memory impairment, and functional and daily-living difficulties. Our report sustains the hypothesis that a iatrogenic form of WE may produce long-term cognitive sequelae even when thiamine therapy is administered in the acute phase until the resolution of the neurological signs.